Handbook of Global Tuberculosis Control Practices and Challenges - Lu, Yichen; Wang, Lixia; Duanmu, Hongjin; Chanyasulkit, Chris; Strong, Amie J.; Zhang, Hui.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2017)
This ambitious reference surveys worldwide efforts at controlling the spread of tuberculosis, with special emphasis on the developing world. Case studies from China, Pakistan, Nigeria, Indonesia, and other frontline countries demonstrate a wealth of information on clinical, cultural, socioeconomic, and other relevant factors. This compilation provides a valuable resource for creating successful intervention and prevention strategies. State-of-the-science snapshots pinpoint where short- and long-term initiatives stand today, from early detection and vaccination programs to new genetic technologies and drug therapies. This diverse group of perspectives and approaches offers innovative paths toward control and realistic odds for containing the threat, especially in the face of current co-epidemics and new drug-resistant strains. Among the topics in the Handbook: Diagnosis of tuberculosis: current pipeline, unmet needs, and new developments Concurrence of tuberculosis and other major diseases The tuberculosis outbreak response, investigation, and control The promise of new TB vaccines DNA fingerprinting of Mycobacterium tuberculosis: a rich source of fundamental and daily applicable knowledge Global tuberculosis surveillance The Handbook of Global Tuberculosis Control is urgent reading for leadership and staff of non-governmental organizations, government agencies, academic institutions, research centers, hospitals, and potentially businesses with interests in tuberculosis control. Additionally, the book's focus on TB in developing countries will attract a wider audience of practitioners, particularly those working in the broader fields of global public health, epidemiology, international development, and the socioeconomics of infectious diseases.
Part I: Global TB SNAPSHOTS -- China (Asia: Category 3) -- India (Asia: Category 4, also including Pakistan, Afghanistan, all SE Asia except Cambodia and Burma) -- Cambodia (Asia: Category 5, also including Burma, North Korea).-Japan (Asia: Category 1) -- Egypt (Africa: Category 1, also including Libya, Tunisia, Western Sahara) -- Algeria (Africa: Category 3) -- Tanzania (Africa: Category 4, also including Angola, Sudan, Chad$1! =(B) -- South Africa (Africa: Category 5, also including all sub-Sahara Africa except Tanzania and Angola) -- Mexico (North America: Category 1, also including US and Canada)Brazil (America: Category 2) -- Honduras (America: Category 3) -- Peru (America: Category 4) -- Iran (Mideast: Category 1) -- Turkey (Europe: Category 2) -- Russia $1!#((BEast Europe: Category 4) -- USA -- Botswana $1!#((BAfrica 5) -- Cuba (America 1) -- Hong Kong (Asia 3) -- Indonesia (Asia 4) -- Nigeria (Africa 5) -- Philippines (Asia 4) -- Senegal $1!#((BAfrica 4 -- Syria $1!#((BMideast 1$1!#) (B-- Part II: Diagnosis, Treatment, and Treatment Management -- Clinical diagnosis of TB: history, current practices, usefulness, defectiveness, and urgent need for new tools -- Current treatment options: history, current practices, effectiveness, limitations, cost of the medicine, access to the medicine, common supplier of the medicine, various market and government supplies, public health services for DOT, and the urgent need for improvement -- A case study: an historic review of DOT in China and future projections -- Drug resistant TB; various causes of treatment failures, identification of drug resistant TB, prognosis and care for drug resistant TB patients, spread and increase of drug resistant TB, threats of drug resistant TB epidemics, future worst and best case scenarios, and the urgent need for new treatment medicines -- A case study: dealing with multiple drug resistant TB in China: current practices and future management strategies -- Treating TB with HIV co-infections and other immune deficiency diseases: difficulties in detecting TB in HIV infected populations, increasing treatment problems associated with ARV treatment with TB co-infections, active TB resulting from organ transplant and other immune suppression, and etc -- A case study: major complications and concomitant disease, Surgery and operative indications, Bronchoscopy and stent, Intensive Care and Rescue of critical illnesses -- New TB diagnosis tool for early detection -- New TB treatment medicine research and development -- A case study: the history and future projection of clinical comparative testing of various TB medical treatment options in China -- Part III: Prevention -- BCG immunization: historical efficacy studies, current global usage of BCG immunization, current immunization coverage, estimated efficacies in different developing countries, the risk and benefit analysis of not using BCG as a vaccine in the US and other developed countries, future perspectives, and the urgent need for more effective vaccines -- A case study: retrospective efficacy evaluation of BCG immunization (comparing TB incidences between comparable populations who received the vaccine and who missed vaccination) -- Latent infections: latent versus active TB, current inability for early detection, risk factors of activating latent infections, examples of local and regional outbreaks, geographic distribution of global latent infections, potential impact on TB control management, and future projections -- Outbreak controls: the most desirable public health responses, identifying and reporting emerging outbreaks, reports, media coverage policies, isolation, detection, medical treatment options, community watches, effective post-exposure surveillance, and etc -- Prophylactic usage of TB treatment medicine to protect newborns and house hold close contacts: practices, effectiveness, problems, and recommendations. Circumstances where a mandatory test is requested: militaries, health care workers, hospital works, students, employment requirement, immigrants, and etc -- A case study: Beijing-strategic plan and implementation of prophylactic usage of TB treatment -- A case study: US-recommended medical practices in prophylactic usage of TB treatment for household close contact groups -- A case study: Pakistan: society awareness and media coverage for TB prevention and treatment) -- New TB Vaccine research and development -- Part IV: Surveillance.-Global TB surveillance system: -- Methodology of estimation of TB incidence and mortality -- TB Socioeconomics: poverty, migration, society changes -- Molecular epidemiology -- A Case study: Korea: Implementation of nationwide TB epidemiology survey -- A Case study : China Web-based TB reporting system -- A Case study: Japan$1!+: (B(same content as in China for direct comparisons).s
Keywords: Medicine; Infectious diseases; Epidemiology; Medicine & Public Health; Epidemiology; Infectious diseases